High-performance Pd nanocatalysts based on the novel N-doped Ti3C2 support for ethanol electrooxidation in alkaline media. (10th September 2021) - Chen, Zhangxin; Yu, Binbin; Cao, Jiajie; Wen, Xiuli; Luo, Minghui; Xing, Shuyu; Chen, Dan; Feng, Chenfu; Huang, Guobo; Jin, Yanxian
Highlights: The novel N -doped Ti3 C2 Pd based catalysts are designed and synthesized. Pd/N-Ti3 C2 -28 h possesses the conspicuous lamellar morphology and uniform metal Pd particles distribution. Pd/N-Ti3 C2 -28 h catalyst exhibit the higher ethanol oxidated current densities, electrochemical stability and cycle stability than the commercial PdC. Our work can provide a new way to consider the other MXene materials as the new catalyst support for direct alcohol fuel cells. Abstract: In this article, the novel N -doped Ti3 C2 support Pd-based catalyst (Pd/N-Ti3 C2 -28 h) is successfully prepared by suitable HF-etching and NH3 . H2 O doping, which possess the conspicuous lamellar morphology and uniform metal Pd distribution. The Pd/N-Ti3 C2 -28 h with N-doping has the higher content of Pd ( 5.33 at%) than that of without N-doping ( 1.38 at%) under the same mass of Pd loading. Being explored as the catalyst for ethanol electrooxidation in alkaline medium, the Pd/N-Ti3 C2 -28 h catalyst exhibits the higher electrochemically active surface areas, ethanol oxidated current densities ( 36.71 mA.cm −2 ) and electrochemical stability than those of the Pd/Ti3 C2 -28 h, the other Pd/N-Ti3 C2 catalysts with different HF-etching time (20, 24 and 32 h), and the commercial Pd/C ( j = 12.73 mA.cm −2 ). Such excellent electrocatalytic performance can be ascribed to synergy of obvious layer-structure of the Ti3 C2 support and the NH3 . H2 O doping, which lead to the higher binding energy and more electron transfer of the metal Pd and Ti3 C2, thereby improving the Pd loading on the Ti3 C2 . And the current densities after 200 redox cycles of Pd/Ti3 C2 -28 h can retain 78.3% of the maximum capacity, demonstrating the high cycle stability. Thus, the Pd/N-Ti3 C2 -28 h can become the potential candidates as the anode catalyst for the ethanol electrooxidation in alkaline medium. Graphical abstract: Image, graphical abstract